Podręczniki prawnicze w ocenie Komisji Konsultacyjno-Naukowej przy Ministrze Sprawiedliwości Z dziejów stalinizacji nauczania prawa w Polsce - Fiedorczyk, Piotr (Z Dziejów Prawa [czasopismo zamknięte], 2020)
The document discussed in this paper was prepared in 1950 by the Scientific-Advisory Committee, which was then operating at the Office of Minister of Justice. It was not released for publication, probably because of its highly controversial content. The Committee was established with an aim to promote Marxist-Leninist ideology in the Department of Justice and the study of law. The document contains the evaluation of fundamental legal textbooks which were the core of teaching law at universities at that time. In fact, it was a form of critique of their authors, the majority of whom did not apply Marxist ideology in their works. It was a most vicious attack and an outright threat against the professors meaning that no other approach would be tolerated. Some of the professors began to comply, but these were in the minority. Others applied the ideol- ogy on a very superficial level. Also, the textbooks of the deceased professors were criticized.